Pengaruh Brand Ambassador Terhadap Keputusan Pembelian Melalui Niat Beli : Studi Pada Brand Scarlett Whitening - Gebi Herry; William Widjaja (Lembaga Pengembangan Kinerja Dosen, 2024)
The current phenomenon is that the entertainment and beauty industry releases many products that can be used by the whole community, so this can create a different culture, encouraging the attraction of celebrity endorsers, who are figures (a person, mascot or group) who are known by the social community and celebrity endorsers. one of them is Twice (K-pop girl group) which is currently collaborating or has an agreement to endorse a brand in the form of Scarlett Whitening skincare products or services. This will influence a brand ambassador on the buyer's decision through the intention to purchase the product, so the author aims to analyze how much influence the brand ambassador has on the buyer's decision through people's purchase intention by using a survey research type method and a quantitative approach as a data collection tool through questionnaires. Data obtained through questionnaires shows that the percentage of women is 84% ​​and the percentage of men is 16%. The results of this research are that brand ambassadors have a positive and significant effect on purchasing interest. Where Scarlett Whitening has superior quality products including consumer trust so it can be concluded that brand ambassadors do not increase purchasing decisions for Scarlett Whitening products. The author gives advice to Scarlett Whitening as the object of this research, even though Twice is already quite good, it still needs to seek more brand awareness and increase consumer trust.